PERLINDUNGAN PEMERINTAH ARAB SAUDI TERHADAP IMIGRAN (TENAGA KERJA) INDONESIA 2010-2012 - Putri, Octariandry Shavita; Nismi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes about The protection of Saudi Arabian’s government towards the immigrants of (labor) Indonesia 2010-2012. The Shipment of Indonesian labor was carried out by the government of Hindia Belanda to Suriname, South America. Difficultly for getting a job in this country to be one of the many factors that Indonesian society decided to work in another country, the country became one of the main options is Saudi Arabia. Initially, Indonesian Labor who worked in Saudi Arabian totaled 25 peoples in 1975, but has decreased from 2010-2012 because of the many cases of abuse committed by employers during work. The research method used is a descriptive of qualitative research method about the facts. This research is an explanatory that describe about problem, indication, policies, and actions. In writing techniques, the author’s collect and collate data through library research from several sources like books, journals, articles, websites, the media and others. The author’s also use the concept of human security in view the case in this study. This research shows the weakness of the Saudi Arabian government protection against existing Indonesian labor in Saudi Arabia from 2010-2012. The weakness of the Saudi Arabian government protection can be seen from the case of poor handling, there are no rules about the protection of domestic workers, the law of Saudi Arabia is different from other countries which use Islamic law or Sharia’ law as the basis of law, and a system of kafala and iqama make the position of domestic workers be difficult.Keywords: Labor, Human Security, Immigrant, Protection